Vineyards in Terraced Landscapes: New Opportunities from Lidar Data. (3rd September 2014) - Tarolli, Paolo; Sofia, Giulia; Calligaro, Simone; Prosdocimi, Massimo; Preti, Federico; Dalla Fontana, Giancarlo
Abstract Vineyard landscapes are a relevant part of the European culture, and several authors concluded that they are the agricultural practice that causes the highest soil loss. Grape quality depends on the availability of water, and soil erosion is an important parameter dictating the vineyard sustainability; therefore, soil and water conservation measures are often implemented. Among them, the construction of terraces is the most widely used system. However, while favouring agricultural activities, terraces if not properly maintained can lead to local instabilities creating hazards for settlements and cultivations, and for the related economy. Terraced fields are also served by agricultural roads that can have deep effects on water flows triggering surface erosion. The goal of this research is to use lidar elevation data for a hydro‐geomorphological analysis of terraced vineyards. The work is divided in two parts. At first, the Relative Path Impact Index is tested in two vineyards to identify terrace‐induced and road‐induced erosions. Statistical thresholds of the Relative Path Impact Index are then defined to label the most critical areas. On the second step, using the index and the defined thresholds, we simulate different scenarios of soil conservation measures, establishing the optimal solution to reduce erosion. The results highlight the effectiveness of high‐resolution topography in the analysis of surface erosion in terraced vineyards, when the surface water flow is the main factor triggering the instabilities. The proposed analysis can help in scheduling a suitable planning to mitigate the consequences of the anthropogenic alterations induced by the terraces and agricultural roads. Copyright © 2014 John Wiley & Sons, Ltd.